Implementation of the Lamikro Application in the Preparation of J'Ramy Farm Financial Statements in accordance with SAK EMKM - Pratiwi, Ratih; Dahliani, Lili; Febrinda, Andi Early; Merdekawati, Eka (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
J'Rami Farm is a dairy farm located in Bogor. In financial management, the owner manually records sales transactions of milk, dairy products as well as expenditures for the purchase of feed, tofu dregs and employee salaries. Meanwhile, expense transactions for overhead costs such as electricity costs, fuel costs, depreciation costs and trade receivables have not been recorded routinely and completely. This causes the financial condition is not known with certainty, because every month the owner has not made a financial report. The purpose of this study was to analyze the implementation of the Lamikro application (micro business accounting reports) in the presentation of financial statements based on SAK EMKM. The Lamikro application is an application created by the Ministry of Cooperatives and SMEs which is expected to assist business people in making financial reports independently and according to SAK EMKM standards. The research methodology used in this study is a qualitative method through interviews and observations. The results showed that the use of the Lamikro application was able to help J'Rami Farm to present bankable financial reports and in accordance with Accounting Standards. The obstacle faced by the owner in using the application is the lack of understanding of accounting, while the limitation of the Lamikro application is that the user cannot edit and add accounts that match the business character of a business.